Prevalence of succinate dehydrogenase deficiency in paragangliomas and pheochromocytomas at Tygerberg Hospital: a retrospective review. - Bruce-Brand, Cassandra (Stellenbosch : Stellenbosch University, 2020)
Thesis (MMed)--Stellenbosch University, 2020.